Pengembangan Aplikasi Penerimaan Siswa Baru Berbasis Web Mobile SMA Negeri 1 Ulu Belu - Muhammad Muslihudin; M Arif Imamudin (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2019)
Acceptance of new students is one of the processes that exist in educational institutions such as schools. New admissions process (PSB) at SMAN 1 Ulu Belu who still use the conventional system, so that prospective students are sometimes difficult to obtain information on the registration process. The registration process also tends to be slow, because the data are not yet integrated and managed. This process also still us the archive in a physical form that is susceptible to damage or even disappear. In order to overcome the problems that occurred in the registration of new students at SMAN 1 Ulu Belu made designing and building applications Admission Information Systems Web-Based Mobile. The method used for the construction of information systems using modeling Entity Relationship Diagram. The result of the design and construction of this information system is the existence of a mobile web-based web that can provide easy access to information and registration processes so that the process of accepting new students becomes more effective and efficient.